Predictors of inadequate minimum acceptable diet among infants and young children in Ethiopia: a multilevel logistic regression analysis - Muluhabt Alene Assfaw; Dereje Tesfaye; Haile Mekonnen Fenta; Wondaya Fenta Zewdia; Bisratgebriel Tesfaye Muchie; Daniel Asmelash (Frontiers in Public Health)
BackgroundInadequate minimum acceptable diet is the cause of poor physical and mental development and poses a significant burden among infants and young children aged between 6 and 23 months. The primary purpose of this study was to determine the factors contributing to inadequate minimum acceptable diet among infants and young children in Ethiopia.MethodThe 2019 Ethiopian Mini Demographic and Health Survey dataset, with 1,463 weighted samples of children aged 6–23 months, was used. Data management was performed using STATA version 17 software, SAS version 9.4, and multilevel analysis. To investigate the determinant factors, we applied multilevel statistical analysis.ResultsAmong 1,246 currently breastfed children aged 6–23 months, based on a 24-h recall method, it showed that 1,066 (85.56%), 550 (44.15%), 1,025 (82.24%), and 1,098 (88.09%) of children had inadequate minimum dietary frequency, minimum meal frequency, minimum milk feeding frequency, and minimum acceptable diet, respectively. The multilevel analysis revealed that individual-level factors, such as mothers with primary, secondary, and higher educational levels, middle and richest household wealth, children aged between 12–17 and 18–23 months, received a postnatal check, and having one and three antenatal care follow-up had lower odds of feeding their children with inadequate minimum acceptable diet than their counterparts. At the zonal community level, children residing in urban areas and children residing in zonal communities with a high literacy level were less likely to have inadequate minimum acceptable diet.ConclusionThere is a high magnitude of inadequate minimum acceptable diet intake among children aged 6–23 months in Ethiopia. Mother’s education, household wealth, marital status, number of families, age of child, postnatal check, community-level education, living in rural areas, and number of people under the age of 5 were significant factors of inadequate minimum acceptable diet. The findings highlight that, to increase the minimum acceptable diet intake in Ethiopia, policymakers and other stakeholders need to prioritize enhancing household wealth status and improving the accessibility of education.